Total Flavonoid Content (TFC) and Antioxidant Activity of Carrot Extract Isolate (Daucus carota L.) - Nadiya Nihlatunnaja; Kalsum, Ummi; Sa’adah, Anifatus (Science and Community Pharmacy Journal, 2023)
Antioxidants are antiradical compounds that can neutralize reactive free radicals into non-reactive ones that are relatively more stable so as to protect cells from the harmful effects of free radicals. Carrots have antioxidant activity due to the presence of carotenoid compounds. This study aims to determine the antioxidant activity of carrots. Extraction research method with maceration method. Isolation of flavonoids by column chromatography method. Antioxidant activity test using FRAP method. The results of research conducted from 60 extract fractions obtained 10 flavonoid fractions with a %TFC value 5,332%; 5,242%; 6,742%; 7,475%; 6,829%; 5,896%; 5,282%; 6,191%; 5,450%; and 5,498%. IC50 3,920; 1,960; 2,096; 2,065; 1,846; 0,867; 3,517; 1,179; 3,383; dan 3,570 ppm. In conclusion, the antioxidant activity of the ten fractions was very strong (<50 g/mL).